Protective effect of HO-1 against oxidative stress in human hepatoma cell line (HepG2) is independent of telomerase enzyme activity - Ghattas, Maivel H; Chuang, Linus T; Kappas, Attallah; Abraham, Nader G (The international journal of biochemistry & cell biology, 2002)
Heme oxygenase-1 (HO-1) is a stress response protein and its induction is associated with protection against oxidative stress. Cell survival during exposure to environmental stresses is associated with elevation of HO-1. Telomerase plays an important role in cell proliferation and immortalization. Our objective was to determine whether the adaptive cellular response to survive exposure to environmental stresses is dependent on expression of HO-1 and telomerase activity in hepatoma cell line (HepG2). Exposure of HepG2 to oxidants, H 2O 2 (100 μM), as well as HO-1 inducers, heme (10 μM) and stannic chloride (SnCl 2) (10 μM), resulted in an increased HO-1 mRNA, protein and total HO activity. On the other hand, HO activity was inhibited by addition of stannic mesoporphyrin (SnMP) (10 μM). These effects were brought about without altering endogenous HO-2 protein levels. Telomerase activity was not affected by oxidants, inducers of HO-1 or inhibitors of HO activity. Similarly, the catalytic subunit of telomerase enzyme human telomerase reverse transcriptase (hTERT), which is considered as the major regulator of telomerase activity, was not affected by oxidants, heme and H 2O 2, or downregulation of HO gene activity by SnMP. This study demonstrates, for the first time, that induction of HO-1 gene mediates protection against oxidants and increases cell survival by a mechanism independent of telomerase enzyme activity. Suppression of HO activity by SnMP decreased cell resistance to oxidant stressors without altering telomerase activity.